Filiation Fatwa on infants less than six months by the Perlis State Fatwa Committee: Technical gaps and implementation measures in Malaysia - Hazni, Nurul Hasna’; Dahlan, Mohd Akram Dahaman (CENTRAL ASIA AND THE CAUCASUS, 2021)
The implementation of filiation in Malaysia is based on the view of Jumhur and Syafii doctrine, that is, the birth of a child is required to be more than six months from the date of marriage of the biological parents. At the same time, the Perlis State Fatwa Committee (JFN) instead decided to come up with a fatwa regarding infants less than six months old. Following this, a study was conducted to examine two objectives, namely, the technical gaps that hinder the implementation of the filiation fatwa by JFN Perlis; as well as its implementation measures in Malaysia. The present study employs qualitative methodology through interviews and archives. The interviews include two members of JFN Perlis and four Syarii Judges from the Perlis Syariah High Court (MTS), MTS Ipoh, Petaling Syariah Subordinate Court (MRS) and MTS Johor Bahru. The archive study involves legal documentation in Malaysia and child certification application files in SHC Perlis from 2009 to 2019. The results of the analysis found that there were four technical gaps in the gazetting of fatwas that hindered implementation. Following this, the steps presented show the methods that can be used in the implementation of fatwas in Malaysia.